CAP Mot : the story of a marine special forces unit in Vietnam, 1968-1969 - Goodson, Barry L., 1949- (War and the Southwest series, 1997)
Based on actual experiences during Barry Goodson's tour of duty in Vietnam from July of 1968 to June of 1969, CAP Mot is the riveting story of one Marine Special Forces unit: "CAP" for "Combined Action Program," and "Mot" for the word "one" in the Vietnamese language. A CAP unit was comprised of six to eight men who lived in the jungles of Vietnam with no firebase or compound for security. Their responsibilities were two-fold. They were to become involved in the everyday.